Combined proteomic and transcriptomic analysis of the antimicrobial mechanism of tannic acid against Staphylococcus aureus - Wang, Jing; Sheng, Zhicun; Liu, Yunying; Chen, Xiaolan; Wang, Shuaibing; Yang, Haifeng (Frontiers in Pharmacology, 2023)
Staphylococcus aureus is a zoonotic opportunistic pathogen that represents a significant threat to public health. Previous studies have shown that tannic acid (TA) has an inhibitory effect on a variety of bacteria. In this study, the proteome and transcriptome of S. aureus were analyzed to comprehensively assess changes in genes and proteins induced by TA. Initial observations of morphological changes revealed that TA damaged the integrity of the cell membrane. Next, proteomic and genetic analyses showed that exposure to TA altered the expression levels of 651 differentially expressed proteins (DEPs, 283 upregulated and 368 downregulated) and 503 differentially expressed genes (DEGs, 191 upregulated and 312 downregulated). Analysis of the identified DEPs and DEGs suggested that TA damages the integrity of the cell envelope by decreasing the expression and protein abundance of enzymes involved in the synthesis of peptidoglycans, teichoic acids and fatty acids, such as murB, murQ, murG, fmhX and tagA. After treatment with TA, the assembly of ribosomes in S. aureus was severely impaired by significant reductions in available ribosome components, and thus protein synthesis was hindered. The levels of genes and proteins associated with amino acids and purine synthesis were remarkably decreased, which further reduced bacterial viability. In addition, ABC transporters, which are involved in amino acid and ion transport, were also badly affected. Our results reveal the molecular mechanisms underlying the effects of TA on S. aureus and provide a theoretical basis for the application of TA as an antibacterial chemotherapeutic agent.